IMPACT OF PRIMARY PROCESSING TECHNIQUES ON THE NUTRITIONAL VALUES OF COMMONLY CONSUMED CEREALS, LEGUMES AND OILSEEDS - MANISHA SHARMA*; S. KOWSALYA (The Journal of Research ANGRAU, 2022)
The objective of this research was to study the impact of processing techniques on the nutrient composition of selected cereals, legumes and oilseeds.The experiment was carried out in the year from January to June, 2021 at Nutrition research laboratory, Avinashilingam Institute for Home Science and Higher Education for Women, Coimbatore. The results revealed that the commonly consumed cereals and legumes after primary processing had significant improvement in terms of nutrients. Moisture content was found to be lowest in pumpkin seeds flour 0.31±0.10g/100g, available carbohydrate was found to be highest in finger millet flour 74.03±0.05g/100g, crude protein was found to be highest in soybean flour 34.06±0.10g/100g, crude fat was found to be highest in pumpkin seeds flour 49.50±0.15g/100g, crude fibre was found to be highest in mung bean flour 6.05±0.06g/ 100g.